Management of urban voids: context, case and propositions. - Montes, Ana Paula (Universidad de Costa Rica, 2016)
The purpose of this review article is to discuss a broaden notion of urban void, in the context of urban sprawl and the urgent need for sustainable land management. To draw a picture about the topic of urban voids, this essay has been divided into two sections. The first part presents a number of concepts that justify a global response of reclaiming urban voids. The second section contains a compilation of case studies of urban void management, whose viability has been possible because innovative urban legislation tools. In the Costa Rican context, where the little discussion about urban voids remain housed in negative urban imaginary, it is important to make visible experiences where its negative meaning has been overcome.